Gap Year Research Fellowship Opportunities for Medical Students Interested in Orthopaedic Surgery. (December 2021) - Clark, Sean C.; Brown, Symone M.; Mulcahey, Mary K.
Abstract : Introduction: Orthopaedic surgery is becoming an increasingly competitive specialty. The purpose of this study was to identify existing orthopaedic research fellowships in the United States and to determine important characteristics including the number of positions offered by each program and the average number of publications from completing the program. Methods: An online search was performed to identify year-long orthopaedic research fellowship programs available for medical students and recent medical school graduates. The number of positions per program and average number of publications of recent program graduates were also obtained. Results: A total of 30 research fellowship programs were identified throughout the United States (13 in the northeast; six in the south; nine in the midwest; and two in the west) that are offered consistently each year. The average number of fellows per program was 3.1 (range 1 to 10) and the average number of publications was 10.8 (range 2 to 20). Conclusion: At least 30 orthopaedic research fellowships in the United States are available to students who are looking to acquire more research experience and strengthen their application for orthopaedic residency. These fellowships can help medical students increase their probability of matching into orthopaedics through publications, networking, and clinical exposure.